Can Problem-Based and Project-Based Learning Improve the Education Quality Control in the Transformation to Online Learning - Ahmed Gaber Abdelhamid Ahmed; R. Madhakomala (Dinasti Research, 2025)
Put an apropriete solution to the disadvantages of lack qulity control in online education; as the online education are growing very fast, world wide, the advanteges push many of learners make it the best choice, like more wide diversity of education program without confine by the learner place, flixable scaduale time, practicing the learning process parallel to practicing the work and so on, but little of student start see the symptom of disadvateges of online learning, by the experience during online study, like social losses,lose indirect learning from teachers, lose respect the education process and so on, Research and developing using relevent articles accredited from aothorised platfoms to find the appropiete data, to find out clear defintions for the problem and the suggested solutions, answer the research problems, and attaine the researsh purposes, Identifying how can use different teaching methode to solve the loose quality control in the online education.